Criminal justice, wildlife conservation and animal rights in the Anthropocene - Sollund, Ragnhild Aslaug 1959-; Lie, Martine S. B. (Bristol University Press, 2024)
This book addresses one of today's most urgent issues: the loss of wildlife and habitat, which together constitute an ecological crisis. Combining studies from different disciplines such as law, political science and criminology, with a focus on animal rights, the chapters explore the successes and failures of the international wildlife conservation and trade treaties, CITES and the BERN Convention. While these conventions have played a crucial role in protecting endangered species from trade and in the rewilding of European large carnivores, the case studies in this book demonstrate huge variations in their implementation and enforcement across Europe. In conclusion, the book advocates for a non-anthropocentric policy approach to strengthen wildlife conservation in Europe
Title from publisher's bibliographic system (viewed on 10 Jan 2025)
Front Matter(pp. i-ii)----Table of Contents(pp. iii-iv)--List of Figures, Tables and Graphs(pp. v-v)--Notes on Contributors(pp. vi-x)--1 Introduction(pp. 1-16)--2 Legal Versus Illegal Hunts: A Species Justice Perspective on Wolf and Bear Theriocides in Norway(pp. 17-35)--3 The Implementation of CITES in Norway: A Longitudinal Approach to the Assessment of Enforcement from a Species Justice Perspective(pp. 36-51)--4 Online Illegal Trade in Reptiles in the Netherlands(pp. 52-69)--5 Countering Wildlife Crimes in Italy: The Case of Bird Poaching(pp. 70-86)--2--Index(pp. 215-222)
Keywords: Animal welfare; Wildlife conservation; Animal rights